Predictions of bimanual self-touch determine the temporal tuning of somatosensory perception - Noa Cemeljic; Xavier Job; Konstantina Kilteni (iScience)
Summary: We easily distinguish self-touch from the touch of others. This distinction is suggested to arise because the brain predicts the somatosensory consequences of voluntary movements using an efference copy and attenuates the predicted self-touch. However, it remains unclear how these predictions impact somatosensory perception before or after the self-touch occurs. Here, participants discriminated forces applied to their left index finger at different phases of the right hand’s reaching movement toward the left hand. We observed that forces felt progressively weaker during the reaching, reached their minimum perceived intensity at the time of self-touch, and recovered after the movement ended. We further demonstrated that this gradual attenuation vanished during similar reaching movements that did not produce expectations of self-touch between the two hands. Our results indicate a temporal tuning of somatosensory perception during movements to self-touch and underscore the role of sensorimotor context in forming predictions that attenuate the self-touch intensity.